Evaluation of the association between acne and smoking: systematic review and meta-analysis of cross-sectional studies (Italian Journal of Public Health, 2010)
Background: Acne vulgaris is one of the most common skin diseases with a multifactorial pathogenesis.Examination of the literature regarding the contribution of smoking to acne shows contradictory results.The aim of this study was to undertake a systematic review of the literature and meta-analysis about theassociation between acne and smoking.Methods: A systematic review and meta-analysis, when possible were performed. The literature reviewwas based on Pubmed, Scopus and Google Scholar searches using the keywords “(smoking OR tobaccoOR nicotine OR cigarettes) AND acne”. Only cross-sectional studies were included. Meta-analyses wereperformed using the RevMan software version 5 for Windows. Four different meta-analyses were carried out:one evaluating the association between smoking habit and acne, one including data stratified by gender, onefor studies with a quality score > 6, and one relating to acne classification.Results: Six studies were selected. The first meta-analysis, including all studies, showed a non-significantrole of smoke in the development of acne: OR 1.05 (95% CI: 0.66–1.67) with random effect estimate. Thesecond meta-analyses, including data stratified by gender, showed a OR=0.99 (95% CI: 0.57–1.73) for malesand a OR of 1.45 (95% CI: 0.08–24.64) for females, using random effect for the heterogeneity in both cases.The third meta-analysis, included studies with a quality score >6 resulted in an estimated OR= 0.69 (95% CI:0.55–0.85): in this case it was possible to use the fixed effect estimate. The last meta-analysis, concerningthe severity grading, showed a non-significant result: OR=1.09 (95% CI: 0.61–1.95) using the random effectapproach.Conclusions: The first two meta-analyses found no signification association between smoking and thedevelopment of acne. However, when we performed the analysis with only good quality studies, theprotective significant effect was evident.
Keywords: acne; smoke; tobacco; nicotine; cigarettes